The Influence of Work Environment and Job Satisfaction on Employee Performance at the Department of Industry and Trade of Central Sulawesi Province - Dasmayanti; Kornelius, Yoberth; Indriani Ibrahim, Andi; Ali Murad, Moh. (Universitas Muhammadiyah Pontianak, 2026)
This study examines the influence of the work environment and job satisfaction on employee performance at the Department of Industry and Trade of Central Sulawesi Province. The objective was to analyze the partial and simultaneous effects of both variables on performance. This research used a quantitative approach with a survey of 61 employees and multiple linear regression analysis. The results showed that the work environment and job satisfaction had positive and significant effects, both partially and simultaneously, on employee performance. These findings imply that improving workplace conditions and employee satisfaction can strengthen organizational performance. Keywords: Work Environment, Job Satisfaction, Employee Performance, Organizational Performance, Public Sector, Multiple Linear Regression